A semiconductor sensor for Cl2 detection and preparation method thereof

By coating the IN2O3/MXENE material on the electrode of the CL2 sensor, the problem of low sensitivity of the existing CL2 sensor and high working temperature are solved, and high -sensitivity detection and room temperature of low concentration CL2 are realized.

CN118961821BActive Publication Date: 2025-01-28TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411442670.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-28
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing Cl2 sensor has a high operating temperature and low sensitivity, making it difficult to detect low concentrations of Cl2.

Method used

Apply the IN2O3/MXENE material on the electrode to improve the sensitivity of the sensor and achieve high -sensitivity testing of low -concentration CL2 gas.

Benefits of technology

The high -sensitivity CL2 detection of working at room temperature has reduced power consumption and can effectively resist the interference of other gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118961821B_ABST
    Figure CN118961821B_ABST
Patent Text Reader

Abstract

The present invention provides a semiconductor sensor for Cl2 detection and a preparation method thereof, belonging to the technical field of gas sensors. The semiconductor sensor for Cl2 detection obtained by the present invention comprises an electrode sheet and a gas-sensitive layer attached to the electrode sheet; the gas-sensitive layer is made of In2O3 / MXene material, and the In2O3 / MXene material is composed of nano-In2O3 and V2CT x The In2O3 / MXene composite material can be obtained by a simple ultrasonic method in the preparation process. This synthesis method is simple, easy to operate, and low in cost. It is selective for the detection of Cl2 and can resist the interference of other gases. It can work at room temperature, greatly reducing power consumption, and has high response sensitivity. It can also achieve high-sensitivity detection of low-concentration Cl2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to a semiconductor sensor for Cl2 detection and a preparation method thereof. Background Art

[0002] Chlorine is a yellow-green toxic gas with a pungent odor. It is widely used in the industrial field and daily life. In industry, chlorine can be used to produce plastics and synthetic fibers. Chlorine is also used as a raw material in disinfectants and bleaches commonly used in life. However, chlorine has serious harm to human health. It can cause damage to the respiratory mucosa. A small amount of chlorine may irritate the eyeballs and upper respiratory tract. Severe chlorine poisoning can cause death. Therefore, it is necessary to research and develop chlorine sensors with good selectivity, fast response speed, simple preparation and can work at room temperature.

[0003] Metal oxide semiconductor gas sensors are widely used due to their low price, wide range of detectable gases, small size and portability. The oxide materials used for gas sensors mainly include SnO2, ZnO2, WO3, In2O3, etc. Among them, In2O3 is cheap to obtain, green and environmentally friendly, and has excellent optical and electrical properties, and is widely used in gas sensors, photocatalysis, solar cells and other fields. When In2O3 is exposed to reducing gas, it undergoes oxidation reaction through chemical adsorption of oxygen species, resulting in reduced resistance; when exposed to oxidizing gas, gas molecules will continue to capture electrons from the conduction band, thereby increasing resistance. However, In2O3 as a gas sensor material has problems such as low sensitivity and high optimal operating temperature.

[0004] However, the current Cl2 sensors have high operating temperatures and low sensitivity, making it difficult to detect low concentrations of Cl2. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a semiconductor sensor for Cl2 detection and a preparation method thereof, wherein the sensitivity of the sensor is improved by coating In2O3 / MXene material on an electrode sheet, thereby achieving highly sensitive detection of low-concentration Cl2 gas.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a semiconductor sensor for Cl2 detection, comprising an electrode sheet and a gas sensitive layer attached to the electrode sheet;

[0008] The gas-sensitive layer is made of In2O3 / MXene material.

[0009] The In2O3 / MXene material is composed of nano-In2O3 and V2CTx Made of MXene composite.

[0010] Preferably, the particle size of the nano-In2O3 is ≤80 nm; the nano-In2O3 can be commercially available.

[0011] Further preferably, the preparation method of the nano-In2O3 is: dissolving In(NO3)3·4.5H2O and sodium citrate in deionized water and stirring, adding urea and ultrasonically dissolving it, and then hydrothermaling the solution at 130~200°C for 20~30 h; collecting the precipitate, washing it with water and ethanol respectively, and then heat treating it at 450~550°C for several hours and then cooling it to obtain nano-In2O3.

[0012] Preferably, the V2CT x The preparation method of MXene is:

[0013] S1: V2AlC is mixed with an etchant and then subjected to ultrasonication, heating, washing and drying in sequence to obtain a first material;

[0014] S2: mixing the first material with dimethyl sulfoxide, stirring, washing and drying in sequence to obtain a second material;

[0015] S3: The second material is mixed with sodium hydroxide solution and then stirred, centrifuged, washed and dried to obtain V2CT x MXene;

[0016] Further preferably, in step S1, the mass volume ratio of V2AlC to the etchant is 1-3 g: 10-50 mL;

[0017] More preferably, the etchant is obtained by mixing sodium fluoride and hydrochloric acid in a mass volume ratio of 1-3 g: 10-50 mL;

[0018] Further preferably, the ultrasonic time in step S1 is 20-30 min; the heating temperature in step 1) is 80-90 °C, and the heating time is 65-72 h:

[0019] More preferably, in step S2, the mass volume ratio of the first material to dimethyl sulfoxide is 0.3-0.5 g: 10-17 mL:

[0020] Further preferably, in step S3, the mass volume ratio of the second material to the sodium hydroxide solution is 0.3 g: 10-50 mL;

[0021] More preferably, the stirring time in step S3 is 2 to 3 h.

[0022] As a preference, the nano-In2O3 and V2CTx The MXene composite method is:

[0023] In2O3 and V2CT x MXene is dispersed in tetrahydrofuran and ultrasonically dispersed for 6 to 10 hours under a nitrogen atmosphere. After the ultrasonication, the precipitate is collected by vacuum filtration and dried in vacuum to obtain In2O3 / MXene material.

[0024] The In2O3 and V2CT x The mass ratio of MXene is 1:1~3.

[0025] In a second aspect, the present invention provides a method for preparing the semiconductor sensor, comprising the following steps:

[0026] The In2O3 / MXene material was placed in an agate mortar and anhydrous ethanol was added for grinding to obtain a gas-sensitive slurry;

[0027] Apply the gas-sensitive slurry on the electrode sheet and wait for it to dry before use.

[0028] Preferably, the mass volume ratio of the In2O3 / MXene material to anhydrous ethanol is 0.001~0.003 g: 0.1~0.3 mL.

[0029] Preferably, the coating amount of the gas-sensitive slurry on the electrode sheet is 0.001 g / cm 2 .

[0030] Preferably, the electrode sheet is one of a Pt electrode, an Au electrode and a Pd electrode.

[0031] Preferably, the drying time is 1 to 2 days.

[0032] Contains at least the following beneficial technical effects:

[0033] 1. In2O3 / MXene composite materials can be obtained by simple ultrasonic method. This synthesis method is simple, easy to operate and low in cost;

[0034] 2. In2O3 / MXene composite materials have a porous structure and a large specific surface area. Coating them on the surface of the electrode sheet can promote the adsorption / desorption and surface reaction of Cl2, have selectivity for the detection of Cl2, and can resist the interference of other gases;

[0035] 3. In2O3 / MXene semiconductor sensors can work at room temperature, greatly reducing power consumption, and have high response sensitivity. They can also achieve highly sensitive detection of low-concentration Cl2. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1The XRD diagrams of the composite materials prepared in Examples 1-3 and Comparative Examples 1-2 are shown.

[0037] Figure 2 The SEM images of the composite materials prepared in Examples 1-3 are shown.

[0038] Figure 3 It is a sensitivity test diagram of the composite materials prepared in Examples 1-3 and Comparative Examples 1-2.

[0039] Figure 4 This is the response diagram of the composite material prepared in Example 2 to different gases. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0041] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0042] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the main idea or essential features of the present invention. Therefore, from all points of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.

[0043] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0044] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.

[0045] Example 1

[0046] This embodiment provides a method for preparing a semiconductor sensor, and the specific steps are as follows:

[0047] 1) Preparation of nano-In2O3: Dissolve 1.5 g In(NO3)3·4.5H2O and 2.5 g sodium citrate in 250 ml deionized water and stir, add 0.6 g urea and ultrasonicate until dissolved, then hydroheat the solution at 150 °C for 25 h; collect the precipitate, wash it with water and ethanol respectively, then heat treat it at 500 °C for 5 hours and cool it to obtain In2O3 with a particle size of 50 nanometers.

[0048] 2) Preparation of MXene:

[0049] S1. Add 2 g of sodium fluoride to 25 mL of hydrochloric acid solution (20%) to obtain an etchant.

[0050] V2AlC (2 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 90 °C for 72 h, and then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0051] S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0052] S3. 0.3 g of the second material was mixed with 25 mL of sodium hydroxide solution (2%) and stirred for 2 h, then centrifuged to obtain the precipitate, rinsed with deionized water, and freeze-dried to obtain V2CT. x MXene.

[0053] 3) Composite nano-In2O3 and MXene:

[0054] In2O3 and V2CT x MXene was dispersed in tetrahydrofuran at a mass ratio of 1:1, and ultrasonically dispersed for 8 hours under a nitrogen atmosphere. After the ultrasonication, the precipitate was collected by vacuum filtration and dried in vacuum to obtain In2O3 / MXene material;

[0055] 4) Preparation of semiconductor sensors:

[0056] 0.002 g of In2O3 / MXene material was placed in an agate mortar and 0.2 mL of anhydrous ethanol was added for grinding to obtain a gas-sensitive slurry;

[0057] 0.001 g / cm 2 The gas-sensitive slurry is applied to the Pt electrode sheet (the electrode sheet area is 1.5 cm 2 ) and use after drying for 2 days.

[0058] Example 2

[0059] This embodiment provides a method for preparing a semiconductor sensor, which is different from the embodiment 1 only in that when preparing the In2O3 / MXene material in step 3), In2O3 and V2CT x The mass ratio of MXene is 1:2.

[0060] Example 3

[0061] This embodiment provides a method for preparing a semiconductor sensor, which is different from the embodiment 1 only in that when preparing the In2O3 / MXene material in step 3), In2O3 and V2CT x The mass ratio of MXene is 1:3.

[0062] Example 4

[0063] This embodiment provides a method for preparing a semiconductor sensor, and the specific steps are as follows:

[0064] 1) Preparation of nano-In2O3: Dissolve 1g In(NO3)3·4.5H2O and 2g sodium citrate in 200ml deionized water and stir, add 0.5g urea and ultrasonicate until dissolved, then hydroheat the solution at 130℃ for 20h; collect the precipitate, wash it with water and ethanol respectively, then heat treat it at 450℃ for 5h and cool it to obtain In2O3 with a particle size of 40nm.

[0065] 2) Preparation of MXene:

[0066] S1. Add 1 g of sodium fluoride to 10 mL of hydrochloric acid solution (20%) to obtain an etchant.

[0067] V2AlC (2 g) was slowly added to the etchant and ultrasonically treated for 20 min, then placed in a Teflon-lined autoclave (50 mL), heated at 80 °C for 70 h, and then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0068] S2. 0.4 g of the first material was dispersed in 15 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0069] S3. 0.3 g of the second material was mixed with 10 mL of sodium hydroxide solution (2%) and stirred for 3 h, then centrifuged to obtain the precipitate, rinsed with deionized water, and freeze-dried to obtain V2CT. x MXene.

[0070] 3) Composite nano-In2O3 and MXene:

[0071] In2O3 and V2CTx MXene was dispersed in tetrahydrofuran at a mass ratio of 1:1, and ultrasonically dispersed for 6 hours under a nitrogen atmosphere. After the ultrasonication, the precipitate was collected by vacuum filtration and dried in vacuum to obtain In2O3 / MXene material;

[0072] 4) Preparation of semiconductor sensors:

[0073] 0.002 g of In2O3 / MXene material was placed in an agate mortar and 0.2 mL of anhydrous ethanol was added for grinding to obtain a gas-sensitive slurry;

[0074] 0.001 g / cm 2 The gas-sensitive slurry is applied to the Pt electrode sheet (the electrode sheet area is 1.5 cm 2 ) and used after drying for 1 day. The average response value was 3%, and the recovery was good.

[0075] Example 5

[0076] This embodiment provides a method for preparing a semiconductor sensor, and the specific steps are as follows:

[0077] 1) Preparation of nano-In2O3: Dissolve 2 g In(NO3)3·4.5H2O and 3 g sodium citrate in 300 ml deionized water and stir, add 1 g urea and ultrasonicate until dissolved, then hydroheat the solution at 200 °C for 30 h; collect the precipitate, wash it with water and ethanol respectively, then heat treat it at 550 °C for 5 hours and cool it to obtain In2O3 with a particle size of 80 nanometers.

[0078] 2) Preparation of MXene:

[0079] S1. Add 3 g of sodium fluoride to 50 mL of hydrochloric acid solution (20%) to obtain an etchant.

[0080] V2AlC (3 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 70 °C for 65 h, and then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0081] S2. 0.5 g of the first material was dispersed in 17 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0082] S3. Mix 0.3 g of the second material with 50 mL of sodium hydroxide solution (2%) and stir for 2 h, then centrifuge to obtain the precipitate, rinse with deionized water, and freeze-dry to obtain V2CT. x MXene.

[0083] 3) Composite nano-In2O3 and MXene:

[0084] In2O3 and V2CT x MXene was dispersed in tetrahydrofuran at a mass ratio of 1:1, and ultrasonically dispersed for 10 hours under a nitrogen atmosphere. After the ultrasonication, the precipitate was collected by vacuum filtration and dried in vacuum to obtain In2O3 / MXene material.

[0085] 4) Preparation of semiconductor sensors:

[0086] 0.002 g of In2O3 / MXene material was placed in an agate mortar and 0.2 mL of anhydrous ethanol was added for grinding to obtain a gas-sensitive slurry;

[0087] 0.001 g / cm 2 The gas-sensitive slurry is applied to the Pt electrode sheet (the electrode sheet area is 1.5 cm 2 ) and used after drying for 1 day. The average response value was 3.4%, and the recovery was good.

[0088] Comparative Example 1

[0089] Preparation of nano-In2O3: Dissolve 1 g In(NO3)3·4.5H2O and 2 g sodium citrate in 200 ml deionized water and stir, add 0.5 g urea and sonicate until dissolved, then hydroheat the solution at 130 °C for 20 h; collect the precipitate, wash it with water and ethanol respectively, then heat treat it at 450 °C for 5 hours and cool it to obtain In2O3 with a particle size of 40 nanometers.

[0090] In2O3 is used as the gas sensitive layer raw material to prepare the semiconductor sensor, and the preparation method is the same as that of embodiment 1.

[0091] Comparative Example 2:

[0092] S1. Add 2 g of sodium fluoride to 25 mL of hydrochloric acid solution (20%) to obtain an etchant.

[0093] V2AlC (2 g) was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a Teflon-lined autoclave (50 mL), heated at 90 °C for 72 h, and then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material;

[0094] S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide (DMSO), and stirred at 20° C. for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain the second material;

[0095] S3. 0.3 g of the second material was mixed with 25 mL of sodium hydroxide solution (2%) and stirred for 2 h, then centrifuged to obtain the precipitate, rinsed with deionized water, and freeze-dried to obtain V2CT. x MXene.

[0096] Using V2CT x MXene is used as the raw material for the gas sensitive layer to prepare the semiconductor sensor, and the preparation method is the same as that in Example 1.

[0097] Experimental Example 1

[0098] The composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to XRD testing. Figure 1 .

[0099] In2O3 and MXene correspond to PDF#29-0101 and PDF#71-2195, respectively. The peak corresponding to the (222) crystal plane in In2O3 and the peak corresponding to the (103) crystal plane in MXene indicate that In2O3 and MXene are of high purity. The composite materials obtained in Examples 1-3 all contain the characteristic peaks of In2O3 and MXene. Examples 1-3 correspond to curves In2O3 / MXene-1, In2O3 / MXene-2 ​​and In2O3 / MXene-3, respectively. It can be observed that with the increase of In2O3 content, the characteristic peak of In2O3 gradually increases.

[0100] Experimental Example 2

[0101] The composite materials prepared in Examples 1-3 were subjected to SEM examination. Figure 2 .

[0102] Figure 2 In Figures ac, they correspond to the composite materials obtained in Examples 1-3, respectively. It can be seen that In2O3 is in the form of nanospheres with a diameter of about 100 nm, and MXene is in the form of phoenix qin flakes. The content of MXene remains unchanged. As the In2O3 doping content decreases, the number of In2O3 nanospheres attached to MXene gradually decreases.

[0103] Experimental Example 3

[0104] The electrode sheets prepared in Examples 1-3 and Comparative Examples 1-2 were placed on the temperature control table of a vessel tester, and the gas sensing performance was tested using an intelligent gas sensing analysis system. At room temperature, the electrode sheets prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to a 0.5 ppm Cl2 cycle test. The results are shown in FIG. Figure 3 As shown, Figure (a) corresponds to Example 2, Figure (b) corresponds to Example 1, Figure (c) corresponds to Example 1, Figure (d) corresponds to Example 3, and Figure (e) corresponds to Example 2.

[0105] It can be seen that Figure (a) shows that the response of MXene is low, the change is not obvious, and the average response value is 0.23%; Figure (b) shows that the response value of In2O3 is large, the average response value is 1.62%, but it is unstable and has poor recovery, and its baseline resistance is high and the power consumption is large; Figure (c) shows that the average response value of the sensor prepared in Example 1 is 1.67%; Figure (d) shows that the average response value of the sensor prepared in Example 3 is 2.28%; Among them, Figure 3 It is shown that the sensor prepared in Example 2 has the highest response value, with an average response value of 4.67%, and has better recovery.

[0106] Experimental Example 4

[0107] The semiconductor sensor obtained in Example 2 was tested for selectivity of different gases. The results are as follows: Figure 4 , Figure 4 (a) shows the resistance-time variation curve of the semiconductor sensor obtained in Example 2 to different gases, the response value of 0.5 ppm nitrogen is about 1.38%; the response value of 1 ppm ammonia is about 2.08%; the response value of 100 ppm hydrogen is about 0.14%; the response value of 100 ppm water is about 0.24%; the response value of 100 ppm methanol is about 0.58%; and the response value of 100 ppm ethanol is about 1.23%. Figure 4 (b) shows the response value comparison of the semiconductor sensor obtained in Example 2 to different gases. Figure 4 (b) It can be seen that its response to Cl2 is the highest, making it suitable as a Cl2 sensor.

[0108] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a semiconductor sensor for Cl2 detection, characterized in that: The following steps are involved: 1) Preparation of nano-In2O3: Dissolve 1.5g In(NO3)3·4.5H2O and 2.5g sodium citrate in 250ml deionized water and stir, add 0.6g urea and ultrasonicate until dissolved, then hydrothermal the solution at 150℃ for 25h; collect the precipitate, wash it with water and ethanol respectively, then heat treat it at 500℃ for 5h and cool it to obtain In2O3 with a particle size of 50nm; 2) Preparation of MXene: S1. Add 2 g of sodium fluoride to 25 mL of 20% hydrochloric acid solution to obtain an etchant; 2 g of V2AlC was slowly added to the etchant and ultrasonically treated for 30 min, then placed in a 50 mL Teflon-lined autoclave, heated at 90 °C for 72 h, then rinsed with deionized water until the supernatant was neutral, and then freeze-dried to obtain the first material; S2. 0.3 g of the first material was dispersed in 10 mL of dimethyl sulfoxide and stirred at 20 ° C for 24 hours, the precipitate was washed with deionized water, and freeze-dried to obtain a second material; S3. 0.3 g of the second material was mixed with 25 mL of 2% sodium hydroxide solution and stirred for 2 h, then the precipitate was centrifuged and rinsed with deionized water and freeze-dried to obtain V2CT. x MXene; 3) Composite nano-In2O3 and MXene: In2O3 and V2CT x MXene was dispersed in tetrahydrofuran at a mass ratio of 1:2, and ultrasonically dispersed for 8 hours under a nitrogen atmosphere. After the ultrasonication, the precipitate was collected by vacuum filtration and dried in vacuum to obtain In2O3 / MXene material. 4) Preparation of semiconductor sensors: 0.002 g of In2O3 / MXene material was placed in an agate mortar and 0.2 mL of anhydrous ethanol was added for grinding to obtain a gas-sensitive slurry; 0.001g / cm 2 Coating amount: Apply the gas-sensitive slurry on an area of ​​1.5 cm 2 on the Pt electrode sheet and use it after drying for 2 days.

Citation Information

Patent Citations

  • V2CTxMXene / In2O3-based sensor material, preparation method thereof and application of V2CTxMXene / In2O3-based sensor material in detection of Cl2

    CN118858386A